Serological relatedness among clinical and environmental Acinetobacter baumannii isolates isolated from hospitals in Baghdad - Hussein, Nadheema; Al-Mathkhury, Harith; Sabbah, Majeed (Iraqi Journal of Science, 2023)
During 2011, 1900 clinical specimens (urine, wounds, burns, blood and sputum) and240 hospital environment specimens were collected from four hospitals inBaghdad/Medical city including: Baghdad Teaching Hospital, The Martyr Gazi Al-Hariry Hospital, Welfare Teaching Hospital and The Burn Specialist Hospital. Allspecimens were cultured and 128 Acinetobacter baumannii were obtained fromclinical and environmental specimens in a ratio of 6.05% (n=115) and 5.42%(n=13), respectively. These isolates were identified using microscopic examination,biochemical tests and Api 20 E system.The slide agglutination technique for rabbitimmune sera and A. baumannii bacteria was used and our data analysis revealed aserological relatedness among the isolates. We found 22 different serotypes for 128clinical and environmental A. baumannii isolates. The most common serotype wasserotype 1 which included 34 isolates (26.56%) and there were 40 (31.25%)miscellaneous isolates which isolated from different specimens, departments andhospitals. Notably, they didn’t arrange within any of the 22 serotypes. Upon suchfindings we may conclude, there is a wide variation in serological characteristics ofthe locally isolated A. baumannii.